(untitled) (Journal of Training and Development, 2019)
Ethics of care, a paradigm for mutual respect, compassion and attention to others in an organization, is considered as the most indispensable and unavoidable for a workplace. Particularly, it is essential in TVET schools as the students are mostly from diverse cultural, family and learning backgrounds and many of them require emotional and psychological support. However, TVET schools are often blamed as care within the schools is yet to be reflected in practice. In this context, a case study was carried out using humanistic paradigm to examine the nature and gravity of ethics of care in TVET schools in Nepal. Data were collected/generated from five TVET schools through prolonged interview by using interview protocol. The data were then analyzed and interpreted with relevant literature and personal reflection. This finding shows that care is imperative to lessen the anxiety and handle the complexities with the students. Care is communicated through language, actions and behaviors. In this regard, the principal maintains a comfortable channel of communication and interacts with the stakeholders to maintain care. However, each principal is unique in their approach of ethics of care. In this context, a discourse or research to explore the differences among the approaches of the principals help them learn from each other.